Peran Pemerintah Nagari dalam Pemberdayaan Masyarakat Melalui Kegiatan Ekonomi Produktif di Nagari Sungai Buluah Kecamatan Batang Anai Kabupaten Padang Pariaman - Nanda Rasifa, Julia; Lanin, Dasman (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research was conducted in Nagari Sungai Buluah, Batang Anai District, Padang Pariaman Regency. The aim was to describe the role of the nagari government in empowering the productive economy in Nagari Sungai Buluah and to find out what the supporting and inhibiting factors were in carrying out this empowerment. This research is a qualitative research with descriptive method. Techniques and data collection through observation, interviews, and documentation. Test the validity of the data using triangulation techniques. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been done, it shows that the role of the nagari government in community empowerment through productive economic activities is not optimal. Viewed from the aspect of the government as a regulator, there is no specific regulation regarding productive economic empowerment in Nagari Sungai Buluah. As a dynamist, namely training and mentoring was only carried out once, namely for 20 days, but the time was not effective due to the discipline of the members. As a facilitator, inadequate facilities and infrastructure to realize productive economic empowerment.